THE NON-RELATIVISTIC LIMIT OF THE RANDALL-SUNDRUM BRANE WORLD MODEL: SOLUTIONS AND APPLICATIONS - Kudinova, A.; Eingorn, M.; Zhuk, A. (Одеські астрономічні публікації, 2011)
The non-relativistic limit of the Randall-Sundrum model with a single brane is investigated. Both exact and approximate expressions for the potential of a delta-shaped material source are used, some geometric configurations of the sources are considered. Formulae for the potential energy and the force of the gravitational interaction are derived, including the most important case of two balls. The constraints on the model’s parameter are obtained.